The Role of Students in Environmental Conservation - Ni Nyoman N. Karmawan; Melani Hotmaida Napitupulu (EXOUSIA : Jurnal Pendidikan Agama Kristen, 2022)
Damage to nature makes the balance of the environment experience inequality, many phenomena of environmental damage occur such as environmental pollution, ecosystem damage and drought. The phenomenon still cannot be resolved, and its impact affects human life. The need to create a sustainable environment in all occupations, especially in the campus world. In the campus world, students lack awareness and environmentally friendly behavior. Therefore, this study aims to describe the level of awareness and behavior of students on campus. This research used a descriptive quantitative method, using questionnaire filling techniques, with a total sample of thirty-five active students on a campus. The results showed that the level of student awareness is included in the High category, but the level of environmentally friendly behavior of students is included in the medium category. The magnitude of the influence of Christian ethics education on nature conservation efforts was 74.3%, while 26.7% was influenced by other factors. This shows that students are already at the conscious stage where environmentally friendly behavior is important, but the implementation is moderate, so that the awareness depicted in students is only limited to theory and is not put into practice.